2011
DOI: 10.1103/physrevb.84.184514
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of multiple-carrier charge transport in the magnetostructurally ordered phase of BaFe2As2

Abstract: We investigated the transport properties of BaFe 2 As 2 single crystals before and after annealing with BaAs powder. The annealing remarkably improves transport properties, in particular, the magnitude of residual resistivity, which decreases by a factor of more than 10. From the resistivity measurement on detwinned crystals, we found that the anisotropy of the in-plane resistivity is remarkably diminished after annealing, indicative of dominant contributions to the charge transport from the carriers with isot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
92
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 25 publications
(56 reference statements)
19
92
2
Order By: Relevance
“…This is reminiscent of other Fe-based compounds. For example, T s of BaFe 2 As 2 was found to increase from 136 K to 142 K on annealing 33 . Such a strong disorder dependence is consistent with an electronically-driven structural transition, often referred to as electronic nematicity in this class of materials.…”
Section: Resistance: Results and Discussionmentioning
confidence: 99%
“…This is reminiscent of other Fe-based compounds. For example, T s of BaFe 2 As 2 was found to increase from 136 K to 142 K on annealing 33 . Such a strong disorder dependence is consistent with an electronically-driven structural transition, often referred to as electronic nematicity in this class of materials.…”
Section: Resistance: Results and Discussionmentioning
confidence: 99%
“…[8,12,13]. The Ru compositions of the samples were determined by energy-dispersive X-ray spectroscopy (EDXS) analysis.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The in-plane resistivity of the twinned samples was measured using a standard four-terminal method. For the measurement of inplane resistivity anisotropy, the crystals were detwinned by applying uniaxial compressive pressure and the resistivity along the a and b axes were measured using the Montgomery method as described elsewhere [12,15,16]. The measurements were performed in a Quantum Design Physical Property Measurement System (PPMS) and all the data were obtained while warming the samples.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a pronounced contribution of parabolic bands to electronic transport has been reported in Shubnikov-de Haas oscillation and Hall coefficient measurements for high quality single crystals made by annealing under BaAs [24,25]. Recent magnetoresistance measurements have reported that the Dirac cone persists in the underdoped regime of Ba(Fe 1−x Ru x As) 2 [26].…”
Section: Introductionmentioning
confidence: 99%